Fiberoptic Bronchoscopy as a Diagnostic Tool in Neonatal Intensive Care Unit: A Single Center Experience - Mohammad Ashkan Moslehi; Farzaneh Fallahi (Mashhad University of Medical Sciences, 2021)
Background: Respiratory disorders are recognized as a leading cause of morbidity and mortality in neonates. Fiberoptic Bronchoscopy (FOB) is used  by pediatricians both for diagnostic and therapeutic indications in children. Nonetheless, there is a paucity of data regarding the diagnostic utility and safety of FOB in neonates, and it has remained relatively under-used in the care of neonates. The present study provided a practical overview of the wide diagnostic aspects of the FOB in newborns hospitalized in the Neonatal Intensive Care Unit (NICU). Frequencies of common indications, their findings, and highlights contribute to the quick management of  neonates with respiratory disorders. Methods: This descriptive study was conducted in the NICU of Namazi hospital and included 150 neonates with various respiratory problems admitted over 5 years within 2013-2018. All subjects underwent FOB and bronchoalveolar Lavage (BAL) using a bronchoscope of 2.8 (EVIS EXERA III Olympus bronchoscope). Results: The greatest indications for performing FOB entailed hypersecretion in 138 (92%) cases, prolonged mechanical ventilation in 108 (72%) neonates, and persistent radiological finding in 97 (64.6%) subjects. Bronchoscopy detected various airways anomalies, such as Laryngomalacia (72%), Tracheobronchomalacia (64%), subglottic stenosis (26%), vocal cord paresis (18%), tracheoesophageal fistula (6.7%), laryngeal cleft (6%),  and laryngeal web (4%). BAL results demonstrated that the cultures were positive in 20 (13.33%) neonates. Acinetobacter was the most commonly reported bacterial infection observed in 8% of neonates. Conclusion: As evidenced by the obtained results, when performed by an experienced and well-trained person and in an environment with appropriate facilities, FOB can be a safe and efficient tool for the early diagnosis of numerous airway disorders among neonates admitted to NICUs.